Decolorization of Synthetic Dyes by Ligninolytic Enzymes from Trametes hirsuta D7 - Anita, Sita Heris; Sari, Fahriya Puspita; Yanto, Dede Heri Yuli (UI Scholars Hub, 2019)
The ability of ligninolytic enzymes from Trametes hirsuta D7 to decolorize several synthetic dyes was investigated. A crude enzyme powder was produced by fermenting oil palm empty fruit bunch fibers for one month. The dye decolorization by the enzymes occurred at an efficient 0.25 U/mL. The enzymes degraded 100, 200, 300, 400, and 500 ppm Remazol Brilliant Blue R (RBBR) within 7 h by 95.57 ± 0.32%, 93.46 ± 3.09%, 91.84 ± 0.65%, 86.44 ± 0.97%, and 82.14 ± 0.52%, respectively. The enzyme also decolorized anthraquinone (Acid Blue 129), monoazo (Acid Orange 7), diazo (Reactive Black 5), and trimethyl methane (Methyl Violet) dyes within 7 h by 94.59 ± 7.97%, 13.99 ± 0.30%, 7.61 ± 0.01%, and 7.59 ± 0.18%, respectively. Addition of MnSO4, H2O2, and violuric acid enhanced the dye decolorization rate by up to 10-fold. This study shows the potential for application of ligninolytic enzymes from T. hirsuta D7 in the treatment of wastewater effluent of textile industries.